2010
DOI: 10.1080/17441690903418969
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based dialogue with communities for district health systems' performance improvement

Abstract: Despite focused health policies and a reform agenda Kenya has not made a breakthrough in improving the situations of households entrapped in the vicious cycle of poverty and ill health. Consequently, Great Lakes University of Kisumu developed and tested a model for facilitating improvement in the performance of the District Health System (DHS) and, hence, the health status of poor households served. The model consisted of evidence-based dialogue between the communities and service providers, working with servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…There are examples where community participation in interventions contributed to efforts to increase provider accountability, for instance when individuals from communities are members of health facility committees [15] or where service statistics are publicised [16]. Providers who do not receive sufficient institutional support such as allowing time for participatory activities and rights-based elements of care, however, are unlikely to prioritise these types of interventions [8, 17].…”
Section: Implementation Considerationsmentioning
confidence: 99%
“…There are examples where community participation in interventions contributed to efforts to increase provider accountability, for instance when individuals from communities are members of health facility committees [15] or where service statistics are publicised [16]. Providers who do not receive sufficient institutional support such as allowing time for participatory activities and rights-based elements of care, however, are unlikely to prioritise these types of interventions [8, 17].…”
Section: Implementation Considerationsmentioning
confidence: 99%
“…There were improvements in a number of indicators, including childbirth in a health facility (41% in intervention sites vs. 23% in control sites, p = 0.000). The authors also report improved accountability of service providers to the communities they served [41].…”
Section: Resultsmentioning
confidence: 98%
“…In Kenya, dialogue between community members and health service providers was a core characteristic of the intervention [41], with actions for improvement agreed between them. In India, community generation of data in maternal death audits drew attention to clusters of deaths in certain geographical areas, and prompted community and health provider responses [29].…”
Section: Resultsmentioning
confidence: 99%
“…Kenya is among the Sub-Saharan African countries that still has a large proportion of its population carrying the highest burden of ill-health (Ministry of Health, 2006;Kaseje et al, 2009). This includes maternal mortality rate of 590 deaths per 100,000 live births in 1998 (Ministry of Planning and National Development, 2005) In the same report (Ibid: 120), it is indicated that 43% of deliveries in Kenya take place under the supervision of skilled attendants.…”
Section: Introductionmentioning
confidence: 99%
“…However, provinces such as Nyanza in western Kenya still register lower proportions of facility deliveries (34 percent). However, the Tropical Institute of Community Health and Development in Africa and Kaseje et al (2009) found that less than one third (30 percent) of mothers use health facility delivery in Siaya district in Nyanza province. Overall, the distribution of mothers that do not deliver under skilled supervision remain high in a number of provinces including North-Eastern (81 percent), Western (73 percent), Rift Valley (66 percent) and Nyanza (54.9 percent).…”
Section: Introductionmentioning
confidence: 99%